Examining the effects of enhanced provider–patient communication on postoperative tonsillectomy pain: protocol of a randomised controlled trial performed by nurses in daily clinical care. Issue 11 (3rd November 2017) - van Vliet, Liesbeth M; van Dulmen, Sandra; Thiel, Bram; van Deelen, Gerard W; Immerzeel, Stephanie; Godfried, Marc B; Bensing, Jozien M
Abstract : Introduction: Placebo effects (true biopsychological effects not attributable to the active ingredients of medical technical interventions) can be attributed to several mechanisms, such as expectancy manipulation and empathy manipulation elicited by a provider's communication. So far, effects have primarily been shown in laboratory settings. The aim of this study is to determine the separate and combined effects of expectancy manipulation and empathy manipulation during preoperative and postoperative tonsillectomy analgesia care on clinical adult patients' outcomes. Methods and analysis: Using a two-by-two randomised controlled trial, 128 adult tonsillectomy patients will be randomly assigned to one out of four conditions differing in the level of expectancy manipulation (standard vs enhanced) and empathy manipulation (standard vs enhanced). Day care ward nurses are trained to deliver the intervention, while patients are treated via the standard analgesia protocol and hospital routines. The primary outcome, perceived pain, is measured via hospital routine by a Numeric Rating Scale, and additional prehospitalisation, perihospitalisation and posthospitalisation questionnaires are completed (until day 3, ie, 2 days after the operation). The manipulation is checked using audio recordings of nurse–patient interactions. Ethics and dissemination: Although communication is manipulated, the manipulations do not cross norms or values of acceptable behaviour. Standard medical care is provided. The ethical committee of the UMC Utrecht and the local OLVG hospital committee approved the study. Results will be published via (inter)national peer-reviewed journals and a lay publication. Trial registration number: NTR5994; Pre-results.